The actions of the Brazilian agricultural sector in the context of climate change negotiations (Sustainability in Debate, 2019)
Brazil has always maintained a prominent position in negotiations within the United Nations Framework Convention on Climate Change, playing a major role in setting increasingly ambitious goals and encouraging consensus among Parties. With the purpose of reducing GHG emissions from the agricultural sector and disseminating and financing good agricultural practices, Brazil developed a platform of sustainable technologies and public policies, as the Low Carbon Agriculture Plan (the “ABC Plan”). This article reviews the main milestones of Brazil’s role in the international negotiation on climate change, how these factors affected the Brazilian agricultural sector between 2009 and 2018 and the authors’ personal view on this context. The objective is to provide an overview of Brazil’s actions regarding the agricultural sector which contribute to the voluntary commitment assumed by the Brazilian government at COPs 15 and 21 and to provide a critical analysis of how these actions are being implemented. The main results show that low carbon agriculture has been consolidated as the main Brazilian strategy for sustainable rural development,but it is vital for our country to continue with these actions.